Lacrimal gland uptake on F-18 florbetapir amyloid positron emission tomography scan - Itani, Malak (Radiol Case Rep, 2017)
In 2012, the Food and Drug Administration (FDA) approved the use of F-18 florbetapir to estimate β-amyloid neuritic plaque density when indicated. A normal scan will show increased radiotracer uptake in the white matter. Mild uptake in salivary glands, skin, muscles, and bones is considered normal. Being a new and infrequently performed study, familiarity with normal biodistribution and variants is important. We hereby present 2 cases with F-18 florbetapir uptake in lacrimal glands. Patients had no symptoms or known systemic conditions to explain this uptake. We speculate that lacrimal gland uptake of F-18 florbetapir could represent a normal variant.